IMPLEMENTASI STRATEGI MARKETING MIX DALAM PEMASARAN JASA PENDIDIKAN DI TK NEGERI 2 YOGYAKARTA - Nurliyati Rahayu (QURROTI, 2020)
The implementation of the marketing mix strategy in marketing education services in TK Negeri 2 Yogyakarta aims to find out how to apply the marketing mix strategy in the kindergarten. The type of research used is qualitative research. Data collection techniques using observation, interviews, and documentation. Data analysis used the Miles and Huberman model which included data presentation, data reduction, and drawing conclusions. The results showed that TK Negeri 2 Yogyakarta used a marketing mix strategy in marketing education services. The marketing mix strategy used is 7P, which consists of: product, price, place, promotion, people, physical evidence, and process. The products offered are multicultural schools with cultural insights. The price offered is very affordable according to the needs of students. The place provided is very strategic. Promotion uses the website as the main promotional media. The available people are very professional and competent. Physical evidence provided is complete and in accordance with the needs of students. The learning process uses four learning models, namely: BCCT, area, angle and safety.